The Moderating Effect of Profitability on The Effect of Liquidity, And Leverage on Financial Distress : (Study of Transportation Sub-Sector Companies on The Indonesian Stock Exchange In 2017-2021) - Hasanah, Umi; Nuansari, Shindy Dwita (DAS Institute, 2024)
His study aims to obtain empirical evidence regarding the Moderating Effect of Profitability on the Effect of Liquidity, and Leverage on Financial Distress (Studies of Transportation Sub-Sector Companies on the Indonesian Stock Exchange 2017-2021). This research was conducted at transportation sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2017 to 2021. A sample of 21 companies was obtained with a total of 105 financial reports. The sampling technique used purposive sampling technique. The data analysis method in this study uses multiple linear regression analysis, MRA (Moderating Regression Analysis), and robustness testing. The results of the study show that (1) there is a significant negative effect simultaneously on financial distress; (2) There is a significant positive effect simultaneously leverage on financial distress; (3) There are profitability results that can strengthen the relationship between liquidity and financial distress; (4) There are profitability results that can weaken the relationship between leverage and financial distress; (5) There are consistent results when adding control variables to financial distress so that the results of the robustness analysis can be said to be robust